Investment-Uncertainty Relationship in the Oil and Gas Industry - Maryam Ahmadi; Matteo Manera; Mehdi Sadeghzadeh (Fondazione Eni Enrico Mattei (FEEM), 2018)
Recent studies on oil market demonstrate endogeneity of oil price by modeling it as a function of consumption and precautionary demands and producers' supply. However, studies analysing the effect of oil price uncertainty on investment, do not disentangle uncertainties raised by underlying components playing a role in oil market. Accordingly, this study investigates the relationship between investment and uncertainty for a panel of U.S. firms operating in oil and gas industry with a new approach. We decompose oil price volatility to be driven by structural shocks that are recognized in oil market literature, over and above other determinants, to study whether investment uncertainty relationship depends on the drivers of uncertainty. Our findings suggest that oil market uncertainty lowers investment only when it is caused by global consumption demand shocks. Stock market uncertainty is found to have a negative effect on investment with a year of delay. The results suggest no positive relation between irreversible investment and uncertainty, but interestingly, positive relation exists for reversible investment. This finding is in line with the option theory of investment and implies that irreversibility effect of increased uncertainty dominates the traditional convexity effect.
Keywords: C3; G11; Q41; Q43; 330; Oil Market; Investment; Uncertainty; SVAR-GARCH